'No perfect image': health, fitness and visual affects with youth after-school. (3rd May 2020) - Safron, Carrie
ABSTRACT: Background and purpose: Messages and initiatives around childhood obesity, health and fitness continue to circulate multiple pedagogical sites (physical education, after-school, media), reproducing a narrow stereotype of the healthy, fit body. While participatory, activist research has offered ways to counter problematic messages that youth receive, much of this scholarship has been set in school contexts. As youth engage with health and fitness across multiple sites, there is a need to investigate possibilities for critical research outside of school. Thus, this paper explores the ways in which five Black and Latinx youth interacted with health and fitness, through visual methods, and the affects produced from these interactions in an urban after-school program in the Northeast region of the United States. Theory: Affect theory, drawing on feminist (Ringrose, Jessica, Katie Warfield, and Shiva Zarabadi. 2019. "Introducing Feminist Posthumanisms/New Materialisms & Educational Research: Response-Able Theory-Practice-Methodology." In Feminist Posthumanisms, New Materialisms and Education, 1–15. London: Routledge) and new materialist (Fox, Nick J., and Pam Alldred. 2017. Sociology and the New Materialism . London: Sage) concepts, frame this paper to consider all bodies (human, non-human) in their interactions. In considering relations between all bodies, affective flows of visual methods, materials and participants were examined to illuminate openings and closings produced by and producing other bodies that can lead to possible change. Methods: While part of a larger visual ethnography, data in this paper were generated from work with five Black and Latinx youth who engaged with visual methods (participant-driven diaries, scrapbooks) during the 'mid-point' of the research project. MacLure's (2013. "Classification or Wonder? Coding as an Analytic Practice in Qualitative Research." In Deleuze and Research Methodologies, edited by R. Coleman, and Jessica Ringrose, 164–183. Edinburgh, UK: Edinburgh University Press) notion of coding was adapted in combination with affect theorizing and Saldana's (2015. Thinking Qualitatively: Methods of Mind . Thousand Oaks, CA: Sage) interpretation of thematic analysis. Themes and discussion: Two themes are presented to illuminate openings and closings that arose from interactions between participants, conversation, visual methods, materials, knowledge and more. These can be considered affective flows and explicate some of the ways that bodies interacted in this research. This research (and these themes), while by no means 'final, ' still offer implications for future practice in urban after-school contexts. I specifically suggest flexible methods and innovative practices be used in after-school programs related to health and fitness, emphasizing a critical approach. I also engage with theoretical and methodological possibilities of a feminist new materialist perspective of affect to alter conventional ways of thinking, doing and practicing health and fitness.